Ukrainians in Michigan - Hedeen, Paul M., 1953-; Hedeen, Maryna (Discovering the peoples of Michigan, 2023)
"This history of Ukrainian immigrants to Michigan and their American descendants examines both the choices people made and the social forces that impelled their decision to migrate and to make new homes in the state"--